2019
DOI: 10.1111/ggi.13695
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of postoperative delirium in older adults using the Confusion Assessment Method for the intensive care unit in non‐intensive care unit settings: A test modification might improve its diagnostic performance

Abstract: Aim To evaluate the diagnostic performance of the Confusion Assessment Method for the intensive care unit (CAM‐ICU) among postoperative older patients in non‐ICU settings. Methods The CAM‐ICU was used by trained staff to prospectively evaluate postoperative patients for delirium. The patients were aged ≥60 years, were in general wards and had no critical illnesses. The assessments occurred for 7 consecutive days after surgery. The results were compared with delirium diagnoses obtained by geriatricians using Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…All participants received standardized perioperative care determined by their clinical treatment teams. Trained clinical research coordinators performed Confusion Assessment of Measurement (CAM) 16 , 17 in the participants on postoperative day 1 and/or 2 between 8:00 am and 12:00 noon to assess POD. Study participants who were diagnosed of POD for at least 1 of the 2 days were in the POD group, those who did not meet diagnosis for POD on either postoperative days were in the No-POD group.…”
Section: Methodsmentioning
confidence: 99%
“…All participants received standardized perioperative care determined by their clinical treatment teams. Trained clinical research coordinators performed Confusion Assessment of Measurement (CAM) 16 , 17 in the participants on postoperative day 1 and/or 2 between 8:00 am and 12:00 noon to assess POD. Study participants who were diagnosed of POD for at least 1 of the 2 days were in the POD group, those who did not meet diagnosis for POD on either postoperative days were in the No-POD group.…”
Section: Methodsmentioning
confidence: 99%
“…Because the longest mean duration of ICU stay was less than 5 days, it was unclear whether part of POD assessments were completed in the surgical ward. It has been shown that performance of POD assessment method is different between ICU and non-ICU sites [3]. Thus, we were concerned that the above unknown factors would have underestimated the incidence of POD reported in this study.…”
Section: To the Editormentioning
confidence: 84%
“…The authors were concerned regarding delirium after the patient left the ICU, and whether we may have underestimated the incidence of delirium in the study. Based on the publication of the fifth edition of the Diagnostic and Statistical Manual of the American Psychiatric Association [3], however, delirium develops over a short period (usually hours to a few days). Indeed, according to our observations, all patients developed delirium on postoperative day (POD) 1, with the longest duration being POD 5.…”
Section: In Replymentioning
confidence: 99%
“…Although CAM-ICU was validated in the ICU setting, delirious symptoms exhibited were still similar symptoms in non-ICU wards. 21 In cases where signs of delirium were present, a psychiatrist conducted a thorough examination and diagnosed based on the criteria outlined in the Diagnostic and Statistical Manual of Mental Disorders, fifth edition (DSM-5). This pragmatic approach ensured a comprehensive and standardized evaluation, given the limitations of available tools in our study setting.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%